Sistem Presensi Dan Penggajian Karyawan Menggunakan Teknologi RFID Dengan Fitur Penggajian Otomatis - Arif Kurniawan; Berkah Yordan Santoso; Desta Aditya; Angga Setiawan; Rudi Susanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
An Employee Attendance And Data Management System Based On Rfid Technology And Api Communication Has Been Successfully Developed And Tested With Satisfactory Results. The Problem Faced Is The Weakness Of Traditional Attendance Methods Which Are Susceptible To Human Error And Time Consuming, Hampering The Productivity And Effectiveness Of Company Operations. The Aim Of Developing This System Is To Increase Efficiency And Accuracy In Recording Employee Attendance. The Method Used In This Research Is The Waterfall Method, Which Includes The Stages Of Requirements Analysis, System Design, Implementation, Testing And Maintenance. At The Needs Analysis Stage, Identification And Documentation Of The Desired Attendance System Requirements Are Carried Out. The System Design Phase Involves Designing The Hardware And Software Architecture, Including The Use Of Rfid With Components Such As The Esp8266, Buzzer, And Rc522 As Well As Integration With The Server Via Api. Implementation Is Carried Out By Developing Hardware And Software According To The Design That Has Been Created. Testing Is Carried Out On Hardware Components To Ensure Function According To Specifications And Hardware-Software Integration To Ensure Smooth Communication Without Delays Or Loss Of Data. Business Logic Testing Ensures The System Detects Absences And Performs Automatic Salary Deductions According To Company Policy. The Data Export Module Was Developed To Export Attendance, Member, Division And Salary Data To An Excel File With The Appropriate Format. The Results Show That The Hardware Components Function Well, Able To Read And Send Rfid Data To The Server Accurately. Hardware And Software Integration Via Api Runs Smoothly, Enabling Real-Time Two-Way Communication. Business Logic Testing Shows That The System Can Detect Employee Absences And Perform Automatic Salary Deductions With High Accuracy. The Data Export Module Proved Effective, Allowing Users To Export Data To An Excel File In An Easily Accessible Format For Further Analysis Or Reporting. The Conclusion Of This Research Is That The Employee Attendance And Data Management System Based On Rfid And Api Technology Has Been Proven To Increase Efficiency And Accuracy In The Employee Attendance And Attendance Management Process. This System Offers A Modern And Effective Solution Compared To Traditional Attendance Methods, Providing Significant Flexibility And Ease Of Access. The Implementation Of This Technology Makes An Important Contribution In The Field Of Human Resource Management, Optimizing Productivity And Operational Effectiveness Of The Company.